The ability of PAM50 risk of recurrence score to predict 10-year distant recurrence in hormone receptor-positive postmenopausal women with special histological subtypes. (2nd January 2018) - Laenkholm, Anne-Vibeke; Jensen, Maj-Britt; Eriksen, Jens Ole; Buckingham, Wesley; Ferree, Sean; Nielsen, Torsten O.; Ejlertsen, Bent
Abstract: Introduction: The Prosigna-PAM50 risk of recurrence (ROR) score has been validated in randomized clinical trials to predict 10-year distant recurrence (DR) in hormone receptor-positive breast cancer. Here, we examine the ability of Prosigna for predicting DR at 10 years in a subgroup of postmenopausal breast cancer patients with special histological subtypes. Methods: Using the population based Danish Breast Cancer Group database, follow-up data were collected on all patients diagnosed from 2000 to 2003 with estrogen receptor (ER)-positive and human epidermal growth factor receptor 2 (HER2) normal breast cancer who by nationwide guidelines were treated with 5 year of endocrine therapy ( N = 2558). Among patients with 1 to 3 positive lymph nodes or a tumor size >20 mm, we identified 1570 with invasive ductal carcinoma (IDC) and 89 with special histological subtypes (apocrine, medullary, mucinous, papillary, secretory, tubular, neuroendocrine) who were tested with Prosigna. Fine and Gray models were applied to determine the prognostic value of the Prosigna-PAM50 ROR score for DR special subtypes as compared to IDC. Results: Median follow-up for DR was 9.2 year and for OS 15.2 year. The 10-year DR rate for the special subtypes was 9.2% (95% CI: 4.0% to 17.2%) as compared to 13.7% (95% CI: 11.9% to 15.7%) for IDC. The 10-year OS was 74.2% (95% CI: 63.7% to 82.0%) for the special subtypes and 75.4% (95% CI: 73.2% to 77.4%) for IDC. Prosigna showed a statistical significant association of the continuous ROR score with risk of DR for both IDC and the special subtypes (IDC: p < .0001; special subtypes: p = .01). Conclusion: In the present study, we demonstrated that Prosigna-PAM50 continuous ROR score added significant prognostic information for 10-year DR in postmenopausal patients with special subtypes (tumor size >20 mm or 1 to 3 positive lymph nodes) and ER-positive, HER2-normal early breast cancer.